Political Ideology and voting:an exploratory study - Scarbrough, Elinor (Oxford, 1984)
In the six years it has taken to complete this book, questions of political ideology have re-emerged with an urgency that belies the prognosis of the end of ideology. In everyday politics, this has been vividly illustrated by events in the wake of the 1979 General Election in Britain: the policy directions of the Conservative government and the break in the Labour Party which ensued followed upon convictions born of political ideologies. In the study of politics, too, the dismissal of ideology from democratic politics confidently pronounced in the 1960s-has been rolled back, largely evidenced in the growth industry of Marxist and neo-Marxist theories of ideology.
Keywords: Voting